Over-Expression of HDA710 Delays Leaf Senescence in Rice (Oryza sativa L.) - Zhao, Nannan; Sheng, Minghao; Zhao, Jie; Ma, Xuelian; Wei, Qiang; Song, Qian; Zhang, Kang; Xu, Wenying; Sun, Chuanqing; Liu, Fengxia; Su, Zhen (Frontiers in Bioengineering and Biotechnology, 2020)
Histone deacetylases (HDACs) influence chromatin state and gene expression. Eighteen HDAC genes with important biological functions have been identified in rice. In this study, we surveyed the gene presence frequency of all 18 rice HDAC genes in 3,010 rice accessions. HDA710/OsHDAC2 showed insertion/deletion (InDel) polymorphisms in almost 98.8% japonica accessions but only 1% indica accessions. InDel polymorphism association analysis showed that accessions with partial deletions in HDA710 tended to display early leaf senescence. Further transgenic results confirmed that HDA710 delayed leaf senescence in rice. The over-expression of HDA710 delayed leaf senescence, and the knock-down of HDA710 accelerated leaf senescence. Transcriptome analysis showed that photosynthesis and chlorophyll biosynthesis related genes were up-regulated in HDA710 over-expression lines, while some programmed cell death and disease resistance related genes were down-regulated. Co-expression network analysis with gene expression view revealed that HDA710 was co-expressed with multiple genes, particularly OsGSTU12, which was significantly up-regulated in 35S::HDA710-sense lines. InDels in the promoter region of OsGSTU12 and in the gene region of HDA710 occurred coincidentally among more than 90% accessions, and we identified multiple W-box motifs at the InDel position of OsGSTU12. Over-expression of OsGSTU12 also delayed leaf senescence in rice. Taken together, our results suggest that both HDA710 and OsGSTU12 are involved in regulating the process of leaf senescence in rice.